Pseudo-occupational asthma. - Venables, K; Davison, A; Browne, K; Newman Taylor, A (1989)
A case is reported in which a pattern of work related asthma in a record of peak expiratory flow was artefactual. The patient had pronounced morning dips, which she recorded on working days, when she made the first recording at 0700 h, but not on holiday, when she stayed in bed longer. The case emphasises the need for clear instructions to patients about peak flow records.